A Static Line Redundant Backup Method Based on Routing Switching Technology - Zheng Dong; Haijun Tang (Dianxin kexue, 2015)
To improve the quality and satisfaction of the government and enterprises network service，the Enterprise Customer Support Center of Nanjing Telecom considers the customer access equipment level，network management skills，customer demand and other factors，with the promotion of maintain service products as an opportunity，innovative created the redundancy methods of static broadband base on routing and switching technology and timely used in the service of the VIP customers，which greatly enhanced the reliability and stability of the network service of the government and enterprises customers.